Effects of pyrimethamine-sulphadoxine, chloroquine plus chlorpheniramine, and amodiaquine plus pyrimethamine-sulphadoxine on gametocytes during and after treatment of acute, uncomplicated malaria in children - A Sowunmi; AA Adedeji; GO Gbotosho; BA Fateye; TC Happi (Memorias do Instituto Oswaldo Cruz, 2006)
The effects of pyrimethamine-sulphadoxine (PS), chloroquine plus chlorpheniramine, a H1 receptor antagonist that reverses chloroquine resistance in Plasmodium falciparum in vitro and in vivo (CQCP), and amodiaquine plus pyrimethamine-sulphadoxine (AQPS) on gametocyte production were evaluated in 157 children with acute, symptomatic, uncomplicated falciparum malaria who were treated with these drugs. PS was significantly less effective than CQCP or AQPS at clearing asexual parasitaemia or other symptoms of malaria. Gametocyte carriage on days 3, 7, and 14 were significantly higher in those treated with PS. The ratio of the density (per µl blood) of peripheral young gametocyte (PYG), that is, < stage III to peripheral mature gametocyte (PMG), that is, stage IV and V, an index of continuing generation of gametocytes, rose to 1 by day 7 of treatment in those treated with PS, but remained consistently below 1 in the other treatment groups. PYG-PMG density ratio increased significantly from day 0-14 in those treated with PS and CQCP (chi2 = 76, P = 0.000001 and chi2 = 42.2, P = 0.00001, respectively) but decreased significantly in those treated with AQPS (chi2 = 53.2, P = 0.000001). Both PS-sensitive and -resistant infections generated PYG (18 of 29 vs 13 of 20, chi2 = 0.04, P = 0.93) but PYG was present only in those with resistant response to CQCP. Combination of PS with amodiaquine (AQ), that is, (AQPS) resulted in less production of PYG, but in this setting, PYG was not indicative of response to AQPS. These data indicate that PS enhanced production or release of young gametocytes when used alone, but generated less young gametocytes when used in combination with AQ. PYG may be used as an indicator of response to CQCP but not PS or PS-based combination drugs.